Tatar-Russian interaction in the Tatar dialects of the Penza region (based on the materials of a dialectological expedition) - Alfiya K. Bulatova (Историческая этнология, 2025)
The Tatars are one of the most ancient peoples of the Penza region. They live compactly in the Belinsky, Vadinsky, Gorodishchensky, Issinsky, Kamensky, Kuznetsky, Lopatinsky, Luninsky, Neverkinsky, Pachelmsky, Sosnovoborsky, Spassky, and Shemysheysky districts. A significant number of Tatars live in settlements with a mixed population. In total, there are about fifty Tatar settlements in the region. The Tatars of the Penza region belong to the Mishari Tatar subethnic group, among whom the western dialect of the Tatar language is widespread. According to the nature of the set of phonetic, grammatical and lexical features, two independent dialects of the Tatar language are distinguished in the region: the Kuznetsk and Temnikovsky dialects of the western dialect. In general, the vocabulary of the Tatar dialects of the Penza region is a holistic lexical and semantic subsystem of the Tatar language diasystem, which has been formed for over several centuries. It has preserved archaic elements, as well as local lexemes. The conditions of centuries-old close proximity of the Tatar population of the studied region with the Russians, and later bilingualism, could not but affect their language. As a result of language contacts, a large number of borrowings from the Russian language entered the speech of the inhabitants. The article presents Russian borrowings that penetrated the dialects of the Tatars of the Penza region, recorded during the scientific expedition of the Institute of Language, Literature and Art of the Tatarstan Academy of Sciences, which took place in 2022. The main research methods applied are the field method of data collection, as well as descriptive (study of factual material, generalization), comparative-historical, and comparative-contrastive methods.